Spatial patterns and temporal trends in mercury concentrations in common loons (Gavia immer) from 1998 to 2016 in New York's Adirondack Park has this top predator benefitted from mercury emission controls? - Schoch, Nina (Ecotoxicology (London, England), 2020)
Mercury (Hg), a neurotoxic pollutant, can be transported long distances through the atmosphere and deposited in remote areas, threatening aquatic wildlife through methylation and bioaccumulation. Over the last two decades, air quality management has resulted in decreases in Hg emissions from waste incinerators and coal-fired power plants across North America. The common loon (Gavia immer) is an apex predator of the aquatic food web. Long-term monitoring of Hg in loons can help track biological recovery in response to the declines in atmospheric Hg that have been documented in the northeastern USA. To assess spatial patterns and temporal trends in Hg exposure of the common loon in the Adirondack Park of New York State, we analyzed Hg concentrations in loon blood and egg samples from 116 lakes between 1998 and 2016. We found spatially variable Hg concentrations in adult loon blood and feathers across the Park. Loon Hg concentrations (converted to female loon units) increased 5.7% yr-1 from 1998 to 2010 (p = 0.04), and then stabilized at 1.70 mg kg-1 from 2010 to 2016 (p = 0.91), based on 760 observations. Concentrations of Hg in juvenile loons also increased in the early part of the record, stabilizing 2 years before Hg concentrations stabilized in adults. For 52 individual lakes with samples from at least 4 different years, loon Hg increased in 34 lakes and decreased in 18 lakes. Overall, we found a delayed recovery of Hg concentrations in loons, despite recent declines in atmospheric Hg